TECNOLOGÍA DIGITAL Y SU EFECTO EN EL DESARROLLO DEL PENSAMIENTO CRITICO DE LA CARRERA PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES –INFORMÁTICA DE LA UNIVERSIDAD TECNICA DE BABAHOYO, PERIODO ACADÉMICO OCTUBRE 2023 - MARZO 2024 - VERA RAMOS YAMILEXIS DAMARIS (2024)
Digital technologies have emerged as a key tool for the development of critical thinking. In this context, a descriptive and qualitative study was carried out to evaluate the effect that digital technologies have on the development of critical thinking of students of the experimental sciences - computer science degree at the Technical University of Babahoyo, academic period October 2023 - March 2024. The sample is 94 students who participated in surveys to learn about the digital technologies they use and the impact they have on the development of critical thinking. The results revealed that the majority of students use social networks frequently for the development of critical thinking, the students also believed that digital technologies such as social networks, information access tools, online learning platforms, blogs and forums Online and digital books positively affect the development of critical thinking, although the majority of students totally agreed, there was a minority who preferred not to give their opinion. In general, the results let us know that digital technologies are essential and positively affect the development of critical thinking, allowing students to gain access to a wide range of information, encouraging critical analysis and the exchange of ideas, which is why It is recommended that teachers include digital technologies in their teaching process.